Hubungan Antara Iklim Organisasi dengan Kepuasan Kerja Karyawan Toko Retail Indomaret di Wilayah Sidoarjo - Ningtita, Nur Arifa Wahyu; Mariyati, Lely Ika (Indonesian Journal Publisher, 2024)
A company is expected to create a comfortable and conducive working atmosphere so that employee job satisfaction can increase and create a good organizational climate. This is the background of this research. This study aims to determine